Improving the efficiency of n-Si/PEDOT:PSS hybrid solar cells by incorporating AuNP-decorated graphene oxide as a nanoadditive for conductive polymers. Issue 42 (28th September 2022) - Van Tu, Nguyen; Anh, Nguyen Ngoc; Van Hau, Tran; Van Hao, Nguyen; Huyen, Nguyen Thi; Thang, Bui Hung; Minh, Phan Ngoc; Van Chuc, Nguyen; Fukata, Naoki; Van Trinh, Pham
Abstract : A GO-AuNP hybrid material was successfully prepared and used for improving the performance of the optoelectronics devices. Abstract : A gold nanoparticle-decorated graphene oxide (GO-AuNP) hybrid material was prepared by using the chemical reduction method. The obtained results showed that the AuNPs of about of 15 nm are well bound on the surface of GO. The GO-AuNP hybrid material was used for transparent conductive film (TCF) and organic/inorganic hybrid solar cells. The TCF based on poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) containing GO-AuNPs was fabricated at room temperature. The obtained results show that the TCF containing 0.5 wt% GO-AuNPs has a high transmittance of 69.7% at 550 nm, a low sheet resistance of 50.5 Ω □ −1 and a conductivity that increased to 3960 S cm −1, which is three times higher than those of the PEDOT:PSS and PEDOT:PSS/GO film. The power conversion efficiency (PCE) of the n-Si/PEDOT:PSS hybrid solar cell containing GO-AuNPs was 8.39% and is higher than pristine PEDOT:PSS (5.81%) and PEDOT:PSS/GO (7.58%). This is a result of the increased electrical conductivity and localized surface plasmon resonance of the PEDOT:PSS coating layer containing the GO-AuNP hybrid material.